Improving interfacial and mechanical properties of glass fabric/polyphenylene sulfide composites via grafting multi-walled carbon nanotubes. Issue 56 (14th October 2019) - Li, Junfeng; Qiao, Yunyun; Li, Dazhe; Zhang, Shengchang; Liu, Pengqing
Abstract : This study reports on the preparation of MWCNTs grafting silanized plain weave glass fabrics (MWCNTs- g -PWGF) to reinforce the interface between PWGF and PPS matrix. The MWCNTs- g -PWGF/PPS exhibits good interfacial compatibility and increased mechanical properties. Abstract : The interfacial strength between reinforced fiber and a polymeric matrix is a critical factor for determining the mechanical properties of composites. Here, grafting multi-walled carbon nanotubes (MWCNTs) onto plain weave glass fabric (PWGF) is introduced to improve the interfacial strength of PWGF reinforced polyphenylene sulfide (PPS) composites. Firstly, MWCNTs-g-PWGF is prepared by grafting oxidized MWCNTs onto functionalized PWGF, and then the MWCNTs-g-PWGF/PPS composite laminates are fabricated by an opening hot pressing process. Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) confirm that the MWCNTs are successfully grafted onto PWGF by chemical linkage. The interfacial morphologies are characterized by scanning electron microscopy (SEM), which reveals a good interfacial compatibility in MWCNTs-g-PWGF/PPS composites. The mechanical properties of MWCNTs-g-PWGF/PPS composites are also characterized by dynamic mechanical analysis (DMA) and universal tensile or bending testing. According to the results, the present method of manufacturing MWCNTs-g-PWGF/PPS composites produces an increase of almost 126% in tensile strength and a significant enhancement of nearly 155% in the bending strength compared with PWGF/PPS composites. The notable increase in the glass transition temperature of MWCNTs-g-PWGF/PPS composites also reflects the remarkable improvement in interfacial strength of the composites.